Delay behaviour of internet router under self-similar traffic via rational approximations. (25th February 2015) - Reddy, D. Mallikarjuna; Dasari, Rajaiah; Perati, Malla Reddy; Reddy, M. Krishna
It has been reported that local area and wide area network traffic exhibit self-similarity and causes degradation of router performance. Therefore, it is crucial for appropriate design of the router. In this paper, first, the router with self-similar input traffic is modelled as MAP/G/1 queuing system and the same is investigated numerically with MMPP/D/1 queuing system. Rational approximations are made from the power series of an irrational function so as to determine its inverse transform thereby to compute virtual waiting time distribution. Numerical results, namely waiting time distribution and mean waiting time against traffic intensity are computed. The analysis presented in this paper is useful in dimensioning the router.